2023
DOI: 10.1177/01979183221149021
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Immigrant Health Trajectories: Disparities in Physical Health Using a Multidimensional Conceptualization of Legal Status

Abstract: Immigrant health research demonstrates that foreign-born individuals generally experience lower morbidity rates relative to native-born individuals. However, this research often overlooks structural factors that influence the immigrant experience, such as legal status. The present study examines legal status as a multidimensional and dynamic characteristic that shapes immigrant health over time. I use two waves of the New Immigrant Survey (n = 3550) to assess if three dimensions of legal status — initial docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Recently, some studies have applied a longitudinal approach to modelling the legal status as a dynamic category for the comparison of migrants who have experienced irregular spells before achieving legal status and those who have continuously experienced legal conditions (Shoumaker et al, 2022 ; Cheong, 2021 ; Jasso, 2011 ; Jasso et al, 2008 ). Previously undocumented immigrants have been observed to obtain less prestigious jobs in the long run (Kreisberg, 2019 ; Molinari et al, 2023 ) and to experience persistent disadvantages in health outcomes (Zajdel, 2023 ). Despite its relevance for investigating receiving contexts where undocumented experiences are widespread—e.g.…”
Section: Legal Status and Immigrants’ Outcomes: Evidence And Methodol...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some studies have applied a longitudinal approach to modelling the legal status as a dynamic category for the comparison of migrants who have experienced irregular spells before achieving legal status and those who have continuously experienced legal conditions (Shoumaker et al, 2022 ; Cheong, 2021 ; Jasso, 2011 ; Jasso et al, 2008 ). Previously undocumented immigrants have been observed to obtain less prestigious jobs in the long run (Kreisberg, 2019 ; Molinari et al, 2023 ) and to experience persistent disadvantages in health outcomes (Zajdel, 2023 ). Despite its relevance for investigating receiving contexts where undocumented experiences are widespread—e.g.…”
Section: Legal Status and Immigrants’ Outcomes: Evidence And Methodol...mentioning
confidence: 99%
“…First, we provide fresh evidence on the role of legal status in shaping fertility patterns of migrant women. Previous studies (almost entirely conducted in the U.S.) have already shown that irregular status affects a variety of immigrant outcomes, from labour market to health conditions (Hall & Greenman, 2015 ; Kossoudji & Cobb-Clark, 2002 ; Zajdel, 2023 ). However, except for a few recent works on the fertility consequences of legalisation and enforcement policies (Amuedo-Dorantes & Arenas-Arroyo, 2021 ; Amuedo-Dorantes et al, 2023 ), limited evidence exists on the relationship between legal status and family dynamics both in the U.S. and Europe.…”
Section: Introductionmentioning
confidence: 99%